Analysis of environmental condition of premices after cruching inside them luminescent lamps - Повстень, В.О.; Дмитруха, Т.І. (Proceedings of National Aviation University (archive), 2010)
The original dependences received and they became a basis for an elaborated calculation way which simplifies determination of environmental condition of premices and levels of risk for poisoning of people after pollution of those premices by dangerous substances, particularly mercury.